2021
DOI: 10.7717/peerj.11661
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of different renin angiotensin system blockade therapies in patients with IgA nephropathy: a Bayesian network meta-analysis of 17 RCTs

Abstract: Background IgA nephropathy (IgAN) is still one of the most prevalent forms of primary glomerulonephritis globally. However, no guidelines have clearly indicated which kinds of renin angiotensin system blockade therapies (ACEIs or ARBs or their combination) in patients with IgAN result in a greater reduction in proteinuria and a better preservation of kidney function. Thus, we conducted a Bayesian network analysis to evaluate the relative effects of these three therapy regimens in patients with I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Numerous Chinese studies have confirmed the safety and efficacy of TCM in the treatment of IgAN ( Li et al, 2020 ; Wang et al, 2021b ). Several meta-analyses have validated the effects of each treatment modality on IgAN ( Zhao et al, 2021b ; Huo et al, 2021 ; Wang et al, 2022 ). It is imperative to investigate an optimal treatment protocol and leverage the complementary and alternative attributes of TCM to ameliorate symptoms, mitigate toxicity and adverse effects associated with contemporary medical interventions, enhance therapeutic efficacy, and diminish the likelihood of recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous Chinese studies have confirmed the safety and efficacy of TCM in the treatment of IgAN ( Li et al, 2020 ; Wang et al, 2021b ). Several meta-analyses have validated the effects of each treatment modality on IgAN ( Zhao et al, 2021b ; Huo et al, 2021 ; Wang et al, 2022 ). It is imperative to investigate an optimal treatment protocol and leverage the complementary and alternative attributes of TCM to ameliorate symptoms, mitigate toxicity and adverse effects associated with contemporary medical interventions, enhance therapeutic efficacy, and diminish the likelihood of recurrence.…”
Section: Introductionmentioning
confidence: 99%